2019
DOI: 10.18203/issn.2454-5929.ijohns20192630
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations of sphenoid sinus among patients undergoing computed tomography of paranasal sinus

Abstract: Background:The approach to sphenoid sinus still remains a clinical challenge, despite the arrival of endoscopy, computed tomography (CT) and functional endoscopic sinus surgery (FESS). The complex and variable anatomy of the sphenoid sinus can be difficult to appreciate with standard axial or coronal CT images of the sinus. The study was done with the objective to study the anatomy of the sphenoid sinus and its variations, and to compare the prevalence of variants obtained in our study with the reported cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The prevalence of the pneumatized anterior clinoid process (22.6%) was higher than the reports in previous Nigerian studies by Fasunla et al, Onwuchekwa and Alazigha, Famurewa et al, and other studies outside Nigeria ( 5 , 6 , 7 , 12 , 18 ) ( Table 4 ). However, Joghataei et al and Gungor and Okur documented higher frequencies in Iran and Turkey respectively ( 2 , 19 ) ( Table 4 ).…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…The prevalence of the pneumatized anterior clinoid process (22.6%) was higher than the reports in previous Nigerian studies by Fasunla et al, Onwuchekwa and Alazigha, Famurewa et al, and other studies outside Nigeria ( 5 , 6 , 7 , 12 , 18 ) ( Table 4 ). However, Joghataei et al and Gungor and Okur documented higher frequencies in Iran and Turkey respectively ( 2 , 19 ) ( Table 4 ).…”
Section: Discussioncontrasting
confidence: 52%
“…Pneumatization of the greater wing of sphenoid and pterygoid process is important to surgeons since it renders the maxillary nerve, vidian nerve, and ICA susceptible to iatrogenic injury and neuralgia in sphenoid sinusitis ( 4 ). The endoscopic endonasal transpterygoid approach to the central skull base uses a pneumatized pterygoid process to access the middle and posterior skull base for biopsy of lesions or repair of CSF leaks ( 7 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Singh (2019) examined 84 CT images and reported the prevalence of pneumatization to the greater wing of the sphenoid and the pterygoid process to be 22.61% and 32.14%, respectively (22).…”
Section: Resultsmentioning
confidence: 99%
“…Of particular note, among limited studies reported from India, Kirtane et al have evaluated the use of vidian neurectomy for crocodile tears, a sequelae lesion of the facial nerve. 24 Bhanu Pratap Singh et al, 25 Sushil Kumar Kashyap et al 26 and Prabu SS 27 have noted protruded and dehiscent vidian canal while studying variations in sphenoid sinus. They have not evaluated the degree of pterygoid process pneumatization.…”
Section: Discussionmentioning
confidence: 99%